Performance of the Village Head in Managing Physical Assets in Sumbersuko Village, Purwosari, Pasuruan - Rossa; Hambali; Siti Adindatus Solikha (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Sumber Suko Village, Kejayan District, Pasuruan Regency has extensive village assets for the village head to manage in support of government. However, the management of these assets is not yet optimal, as can be seen from the large number of village physical assets that are in disrepair. The main problem in this management is asset planning and monitoring that has not been optimal. This research aims to measure the performance of village heads in managing village physical assets using qualitative methods with observation, interviews and documentation, as well as data analysis by Miles & Huberman. George R. Terry's performance management theory approach—including planning, organization, implementation, and monitoring—is used as an analytical framework. The research results show that the performance of village heads is inadequate, as evidenced by the large number of assets that are stalled, lost or damaged due to weak planning and supervision.